Elementary school student digital literacy framework: A Confirmatory Factor Analysis (CFA) - Ari Wijayanti; Siti Irene Astuti Dwiningrum; Bambang Saptono; Mohammad Archi Maulyda (Ricerche di pedagogia e didattica, 2025)
This research aims to produce a digital literacy framework for elementary school students. This framework refers to Indonesia’s Digital Literacy Roadmap 2020-2024. A total of 28 indicators were adopted as a digital literacy framework for elementary school students. Furthermore, a confirmation factor analysis (CFA) was using 209 respondents of elementary school students. Based on the results of the initial CFA, the structure of the factors formed is fit. However, to obtain the structure of these factors, researchers must delete many items, thus giving rise to the assumption that there needs to be clarity in the structure of the factors formed. The researcher conducted an Explanatory Factor Analysis (EFA) test to obtain a new factor structure. After that, a second CFA test was carried out. Based on the results of the final CFA, 19 items were found whose factor structure was fit and became the framework for elementary school digital literacy.